Glass Ceiling or Sticky Floor? Exploring the Australian Gender Pay Gap using Quantile Regression and Counterfactual Decomposition Methods - Kees, H (My University, 2005)
Using the HILDA survey, this paper analyses Australian gender wage gaps in both public and private sectors across the wage distribution. Quantile Regression (QR) techniques are used to control for various characteristics at different points of the wage distributions. Counterfactual decomposition analysis, adjusted for the QR framework, is utilised to examine if the gap is attributed to differences in gender characteristic, or differing returns between genders. The main finding is that a strong glass ceiling effect is detected only in the private sector. Secondly, the acceleration in the gender gap across the distribution does not vanish even after extensive controls. This suggests that the observed wage gap is a result of differences in returns to genders. By focussing only on the mean gender wage gap, substantial variations of the gap will be hidden.
Centre for Economic Policy Research, Australian National University Discussion Paper
Keywords: Finance; Finance -- Income (Salary and Wages); Gender; Income, wealth and finances; Income, wealth and finances